(untitled) (Asian Education Studies, 2018)
Globalisation and internationalisation have brought culturally diverse classrooms into universities and schools worldwide. There are increasing opportunities for culturally diverse teachers and students to interact and learn from each other. This paper investigates the changes that occur when classrooms are managed by teachers with different cultural backgrounds from that of their students, utilising observations and interviews. The research indicates that when people from both collective and individualist cultures are in the same classroom, the different dynamics require adjustments from at least one cultural group to achieve desirable learning outcomes, in particular from the teacher. This is largely due to, in individualistic and collective cultures, teachers having different roles associated with their respective power structure and social hierarchy caused by various ways of establishing and maintaining individual self-esteem and perceiving self in relation to others. It would appear that the changes are engineered by a teacher’s desire to allow students to learn more effectively and teachers’ belief as to what are effective teaching and learning strategies. However, the changes are also accompanied by many challenges and personal growth on the part of the teachers. Bridging cultural differences should never been taken for granted. Should teachers reflect deeply and adjust to changes in classroom culture, the learning and teaching experiences can be both enriching and enlightening. Intellectual challenges and reflections on different home and host cultural assumptions are required when managing students who are from dissimilar cultural backgrounds.